Narratives about Venezuelan migrant women in an online newspaper from the Colombian border - Espinel Rubio, Gladys Adriana; Mojica-Acevedo, Eliana Caterine; Niño-Vega, Nohora Constanza (Estudios sobre el Mensaje Periodístico, 2021)
This article identified the narratives that La Opinion.com.co (the online version of a newspaper from Cúcuta, Colombia, the main city on the Colombian-Venezuelan border) made about Venezuelan migrant women from 2015-2020. Through the content analysis of 134 notes, it was determined that the media reports migrants as vulnerable, with little agency capacity and whose strengths are based on sex work or the involvement of criminal acts. Women are protagonists in the binomial agents or victims, identifying three narrative lines: the victims and agents of the border crisis; murder victims and criminals, and lastly, victims of prostitution and trafficking in persons for sexual exploitation and prostitutes. In conclusion, it has constructed precarious narratives of the Venezuelan migrant woman associated with the dangerous, the sick or the contagious.